(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study examined the phonotactics of consonant clusters in English as well as its complexity at the onset and coda positions in words. It determined that English words exhibit consonant clusters up to three at onset and up to four at the coda. The study restricted itself to the performance ability of Akwa Ibom English bilinguals in the production of consonant clusters. The Stratified Random Sampling Technique was adopted in the selection of thirty respondents in Senior Secondary Two (SS2) class. The instrument contained a short passage and sixty words where the respondents were made to read aloud into an audio device. The data were analyzed perceptually using simple percentage. The results thereby showed that Akwa Ibom English bilinguals do not have difficulty in the production of word-initial consonant clusters but they have difficulty in the production of word-final consonant clusters, especially when it has to do with certain combinations. The study concluded that Akwa Ibom English bilinguals demonstrate cases of reduction and simplicity at coda consonant clusters, and a slight epenthesis where there are vowel letters but with no sounds.